The Legal Underpinnings of Medical Discipline in Common Law Jurisdictions. Issue 1 (2nd January 2019) - Gallagher, Cathal T.; Hussain, Kasim; White, Jessica D. P.; Chaar, Betty
Abstract: Medical regulators have a responsibility to protect, promote, and maintain the health and safety of patients. Here, we compare and contrast the processes for addressing concerns about doctors in four countries with legal systems based on English common law: the UK, Australia, the United States, and Canada. The legal provisions underpinning each jurisdiction's disciplinary processes depict distinctive outlooks from the different authorities as each works toward the same goal. The initial stages of the investigation process are broadly similar in all of the jurisdictions examined. Each process, however, has subtle differences with regard to its comparators. Factors include how matters of discipline are framed, the constitution of disciplinary panels, and how the perceived independence of these panels all philosophically affect the public safety remit of each regulator. This work constitutes the first comparison of international regulatory frameworks for the profession of medicine.